Peer Observation in Facilitating Teacher Professional Development: A Study of EFL Novice and Experienced Teachers Perceptions - Indah Dwi Lestari; Utami Dewi (STAI Hubbulwathan Duri, 2022)
Novice and Experienced English Teachers are inevitably confronted with a must to be a qualified and professional teacher. This is particularly relevant in Indonesia, where English teachers are graduates of English Education departments has challenged to teach not only English language, but also culture and should have preparation for their duties as English teachers. Peer observation has the potential to facilitate teachers to develop their teacher professional development, particularly those who teach EFL in navigating challenging elements of their teaching practice. For this reason, this qualitative study explored 10 participants’ perceptions of peer observation as an aid to professional growth. Data were garnered from questionnaires and in-depth interview. The findings of the study suggest that the participants’ understanding of peer observation as an opportunity for them to learn each other to improve their teaching quality and construct their professional identity. Then, the participants also talk about their experiences in doing peer observation, which Experienced Teachers (ET) are more confidence than Novice Teachers (NT). Further, both ET and NT need peer observation to negotiate issues and solve problems. Finally, peer observation enabled the participants to reflect on themselves and their respective weaknesses in teaching English for professional development as both novice and experienced teachers.